Monitoring of Antibiotic Residues in Chicken Meat, Cow and Buffalo Milk Samples in Nepal - Gompo, Tulsi Ram; Sapkota, Ramchandra; Subedi, Manita; Koirala, Pragya; Koirala, Pragya; Bhatta, Diker Dev (International Journal of Applied Sciences and Biotechnology, 2020)
In animal products, the antibiotic residue is a serious concern to public health in the Himalayan nation, Nepal. A cross-sectional study was conducted to estimate antibiotic residues in meat samples of chicken and milk samples of cows and buffaloes from different districts of Nepal. An equal number of chicken meat samples, 42 each from Kailali (Farwestern Province), Kaski (Gandaki Province), and Nuwakot (Bagmati Province) districts were tested for tetracycline, sulphonamides, penicillin, gentamicin and streptomycin residues by the application of the ELISA method. At Kaski district, approximately 57% (24/42), 50% (21/42) and 83% (35/42) of the samples were tested positive for gentamicin (mean-ppb:11.5 μg/Kg/L), tetracycline (mean-ppb:1.44 μg/Kg/L), and fluoroquinolones (mean-ppb:11.46 μg/ Kg/L) residues, respectively. In Kailali, 48% (20/42) of meat samples were tested positive for sulphonamides (mean-ppb:15.9 μg/ Kg/L) and in Nuwakot, 50%(21/42) of meat samples were tested positive for penicillin (mean-ppb: 0.39 μg/ Kg/L). Of the total 168 tests performed in the milk samples of Kavre district, on average, 55% (93/168) were detected with the antibiotic residues for gentamicin, streptomycin, and sulphonamide. The antibiotic residues in chicken meat were within the national maximum residue limit (MRL); however, milk samples exceeded the national MRL for sulphonamide residues (mean-ppb: 26.44 μg/ Kg/L). Effective surveillance for antibiotic residues should be implemented strictly on animal products in Nepal. Int. J. Appl. Sci. Biotechnol. Vol 8(3): 355-362